2019
DOI: 10.3389/fimmu.2019.01625
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of HLA-presentation of Non-synonymous Recipient Mismatches Indicates Effect on the Risk of Chronic Graft-vs.-Host Disease After Allogeneic HSCT

Abstract: Genetic mismatches in protein coding genes between allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipient and donor can elicit an alloimmunity response via peptides presented by the recipient HLA receptors as minor histocompatibility antigens (mHAs). While the impact of individual mHAs on allo-HSCT outcome such as graft-vs.-host and graft-vs.-leukemia effects has been demonstrated, it is likely that established mHAs constitute only a small fraction of all immunogenic non-synonymous variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…SNP disparities in the same range have been reported by others (37). Martin et al (40) showed that a higher number of SNP disparities in patients transplanted with sibling donors was associated with an increase in grade III-IV GVHD and stage 2-4 acute gut GVHD, whereas Ritari et al (41) found an association between a higher number of mismatching peptide ligands and chronic GvHD. All SNP disparities as measured by Koparde et al (39) were also investigated to encode 9-mer peptides with predicted binding to patients' HLA class I alleles using NetMHCpan 2.8.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…SNP disparities in the same range have been reported by others (37). Martin et al (40) showed that a higher number of SNP disparities in patients transplanted with sibling donors was associated with an increase in grade III-IV GVHD and stage 2-4 acute gut GVHD, whereas Ritari et al (41) found an association between a higher number of mismatching peptide ligands and chronic GvHD. All SNP disparities as measured by Koparde et al (39) were also investigated to encode 9-mer peptides with predicted binding to patients' HLA class I alleles using NetMHCpan 2.8.…”
Section: Discussionsupporting
confidence: 66%
“…Whole transcriptome RNA sequencing and HLA ligandome analysis by mass spectrometry can be implemented as additional steps to select for peptides that are expressed and presented on the cell surface. These techniques significantly decrease false discovery (31,38,41,42), but also reduce the sensitivity and lead to a higher chance that antigens are missed (38), illustrating that prediction tools for minor histocompatibility antigens still require optimization.…”
Section: Discussionmentioning
confidence: 99%
“…We discovered pathways associated with aGvHD pathogenesis, implicating immunological responses in processes such as T cell function, cytokines, JAK-STAT signaling, and regulation of the TRAF6 gene. The risk for GvHD has mainly been investigated during past decades by concentrating on the MHC region and specific candidate genes (10,11), and only in recent years has the use of genome-wide approaches emerged in the field (16,17,(19)(20)(21)(22). These studies have shown the importance of genetic component in HSCT complications, but the results remain diverse, and their replication is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained no results for cGvHD, which may be due to the smaller number of available studies or lack of strong genetic component in this condition. We recently reported that the severity of cGvHD is associated with the overall immunogenetic differences between HSCT pairs (22); hence, its genetic background may differ from that of aGvHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation